Concerns and coping styles in adolescents from Lima - Martínez, Patricia (2001)
Combining qualitative and quantitative methodology, the study describes the main concerns of a group of adolescents and the strategies they use to cope with such concerns according to socio-demographic variables (age, sex and type of school). It is a descriptive study, with a transsectional design, of 413 adolescents from 13 to 18 years. The used instrument was the specific form of the Adolescent Coping Scale (ACS) (Frydenberg & Lewis, 1997) that included oneopen question regarding their main concern. It was found that their major concerns are centeredin their future and school performance and that the most used coping strategies were Concernand Work Hard. It was found that socio-demographic variables make important differences among the different groups.